EFEKTIVITAS PELAKSANAAN PROGRAM URBAN FARMING DI KELURAHAN MEDOKAN AYU KECAMATAN RUNGKUT KOTA SURABAYA - Maijun; Sasmito Jati Utama (Faculty of Social and Political Science, 2013)
This research is a descriptive study using qualitative methods. The research is based on the phenomenon that was discovered a few obstacles in the implementation mechanism Urban Farming Program in the city of Surabaya. The research was conducted in the District Rung/cut, where District Rungkut are districts with the highest number of poor families based on total area in 2010, and focused on the Village Medokan Ayu based on the total number of recipients of aid packages from 2009 to 2010.The purpose of this study is to analyze how the effectiveness of the implementation of urban farming catfish aquaculture in the Village District Rungkut Sub Medokan Ayu Surabaya. The theory used is the theory of the effectiveness of programs that are used to determine the effectiveness of the implementation of the urban farming program. Data was collected by observation interviews, and analyzing the data contained in the photo archives and documentation activities in the Village Raising catfish Medokan AyuXlonclusionThe results of this research is the implementation of the program overall urban farming catfish aquaculture in Sub Medokan Ayu less effective because the program has yet to impact on the welfare of the poor. It is seen from socialization activities, where dissemination activities liave been carried out, but the understanding of program participants is low. thus resulting in a failure in the process of cultivation. Seen from the program's objectives have not been able to reduce poverty by fish farming activities, the program is still not optimal in a narrow land into productive land. Productive employment opportunities to the urban farming program implemented but not implemented sustainable society, and the purpose of the program in increasing the revenue has not yet been able to increase the incomes of the poor.